Primary family caregivers of children with cancer and their available social support in Cartagena (Colombia) - Montalvo-Prieto, Amparo Astrid; Peluffo-Mendoza, Yenifer Tatiana (Universidad y Salud, 2020)
Introduction: Social support for caregivers of children with cancer is a source of help that strengthens them to face this situation. Objective: To determine the association between sociodemographic and care conditions with the perceived and actual social support received by primary family caregivers of children with cancer in two health institutions in Cartagena-Colombia. Materials and methods: Cross-sectional analytical study with 126 caregivers, using cronica© and Duke-UNK-11 instruments to characterize family caregivers of people with chronic diseases. The results are presented in absolute and relative values and the associations are shown as Odds ratio. Results: 42.9% of caregivers function alone, with ages between 18 and 59 years. 78.8% are women and 56.3% have been caregivers for more than 19 months, of which 94.4% have been caregivers since the diagnosis. 50% serve as caregivers all day, 38.9% report that social support is scarce, 75.4% that support is confidential and 23% report it as affective. Conclusions: Being a caregiver causes loneliness, fatigue and neglect of their own care. Even though emotional support of caregivers becomes an important resource to strengthen them, the participating caregivers did not perceive it. Leadership is required to foster values of coexistence and make social support available for caregivers.